1968
DOI: 10.1071/bi9680619
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphorus and Zinc Levels in The Substrate on 65Zn Distribution in Subterranean Clover and Flax

Abstract: Subterranean clover ( Trifolium subterraneum L.) and flax (Linum usitatissimum L.) were grown in water cultures containing 65Zn and all combinations of deficient or normal zinc supply and low or excess phosphate levels. 65Zn distribution in the plants was determined by autoradiographs and radioassays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1969
1969
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…They further reported (Riceman and Jones 1960) that the zinc in fully expanded leaves was largely retained, and it was only when these leaves became prematurely senescent as a result of zinc deficiency that any of this zinc was retranslocated. Millikan, Hanger, and Bjarnason (1968) also observed a similar removal of 65Zn from senescent old leaves in zinc-deficient T. subterraneum. The reason for the release of zinc from zinc-deficient senescing leaves is not known.…”
Section: Discussionsupporting
confidence: 51%
“…They further reported (Riceman and Jones 1960) that the zinc in fully expanded leaves was largely retained, and it was only when these leaves became prematurely senescent as a result of zinc deficiency that any of this zinc was retranslocated. Millikan, Hanger, and Bjarnason (1968) also observed a similar removal of 65Zn from senescent old leaves in zinc-deficient T. subterraneum. The reason for the release of zinc from zinc-deficient senescing leaves is not known.…”
Section: Discussionsupporting
confidence: 51%
“…The cause of P-induced Zn deficiency has intrigued many researchers and several explanations have been proposed, including the theory that P enhances the physiological requirement for Zn (Millikan et al, 1968), or inactivates Zn in the tissues (Leece, 1978), but the actual causal mechanism is still unknown (Payne et al, 1986). One of the controversies is why P treatment enhance symptoms of Zn deficiency without a proportional decline in Zn concentrations of plant tissues (Olsen, 1972), as evident in Table 3.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…Moreover, high levels of Pin this experiment decreased the concentration ofZn in plant tissue near critical levels (Table 3). Other explanations are based on the translocation of Zn from roots to shoots (Stukenholtz et al, 1966;Sharma et al, 1968;Safaya, 1976) or metabolic anomalies, which are caused from a lack of equilibrium between two elements in the plants (Boawn and Leggett, 1964;Boawn and Brown, 1968;Millikan et al, 1968). The latter has been clarified through the work of Loneragan et al ( 1982) who have shown that Pinduced Zn deficiency is not due to Zn metabolism in the leaves, but rather on P absorption and transport from roots.…”
Section: Nutrient Distribution In the Foliagementioning
confidence: 99%